2021
DOI: 10.1108/jaoc-06-2020-0079
|View full text |Cite
|
Sign up to set email alerts
|

The influence of an interactive use of management control on individual performance: mediating roles of psychological empowerment and proactive behavior

Abstract: Purpose Although middle managers play important roles in forming strategies and generating innovation, few studies have explored the influence of management control systems (MCS) on employees’ behaviors or performance at the middle-management level. The purpose of this study is to examine the effect an interactive use of MCS has on individual performance at the unit level. Design/methodology/approach A longitudinal, multisource and multilevel survey was conducted among 373 nurses in 20 units at a Japanese pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
28
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(37 citation statements)
references
References 89 publications
6
28
0
3
Order By: Relevance
“…The hypothesis was supported (β = 0.477; p < 0.001). The result corroborates studies on MCS that support the beneficial role of interactive (Matsuo et al, 2021) and enabling controls (Baird et al, 2018; in psychological empowerment. This result, especially within the scope of informal controls, broadens the understanding of their positive effects on organizational commitment (Goebel & Weißenberger, 2017a), participation (Wohlgemuth et al, 2019), and organizational identification by employees (Monteiro & Lunkes, 2021), by highlighting positive effects on psychological empowerment.…”
Section: Discussion Of the Findingssupporting
confidence: 88%
See 4 more Smart Citations
“…The hypothesis was supported (β = 0.477; p < 0.001). The result corroborates studies on MCS that support the beneficial role of interactive (Matsuo et al, 2021) and enabling controls (Baird et al, 2018; in psychological empowerment. This result, especially within the scope of informal controls, broadens the understanding of their positive effects on organizational commitment (Goebel & Weißenberger, 2017a), participation (Wohlgemuth et al, 2019), and organizational identification by employees (Monteiro & Lunkes, 2021), by highlighting positive effects on psychological empowerment.…”
Section: Discussion Of the Findingssupporting
confidence: 88%
“…In turn, highlighted that an enabling perception of MCS leads to psychological empowerment, which induces managers' organizational resilience. Finally, Matsuo et al (2021) found that the interactive use of MCS positively affects employees' psychological empowerment, proactive behavior, and performance.…”
Section: Informal Controls and Psychological Empowermentmentioning
confidence: 96%
See 3 more Smart Citations